Good and ought in argumentation - Ruiz, Andrés (2022)
UIDB/00183/2020 UIDP/00183/2020 This publication is based upon work from COST Action CA-17132 European Network for Argumentation and Public Policy Analysis (http://publicpolicyargument.eu), supported by COST (European Cooperation in Science and Technology).